2017
DOI: 10.1007/s10113-017-1194-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling population structure in the context of urban land use change in Europe

Abstract: Population structure and dynamics are important drivers of land use. In this article, we present the methods and outcomes of integrating population projections across multiple spatial scales with an urban growth model. By linking shared socioeconomic pathway (SSP)-specific national population projections to present-day population distributions at a sub-national scale, we describe a downscaling approach that provides input into a regional urban growth (RUG) model for Europe. The allocation of population acts as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…The IAP The impacts and risks from high-end scenarios: strategies for innovative solutions (IMPRESSIONS) IAP is an interactive web-based platform to assess climate change impacts, vulnerability and adaptation [28,[33][34][35][36]. The platform integrates a series of interlinked meta-models representing urban development [37,38], water resources [39], flooding [40], forests and agriculture [41], and biodiversity [42] (supplementary figure SF1 is available online at stacks. iop.org/ERL/14/104009/mmedia).…”
Section: Methodsmentioning
confidence: 99%
“…The IAP The impacts and risks from high-end scenarios: strategies for innovative solutions (IMPRESSIONS) IAP is an interactive web-based platform to assess climate change impacts, vulnerability and adaptation [28,[33][34][35][36]. The platform integrates a series of interlinked meta-models representing urban development [37,38], water resources [39], flooding [40], forests and agriculture [41], and biodiversity [42] (supplementary figure SF1 is available online at stacks. iop.org/ERL/14/104009/mmedia).…”
Section: Methodsmentioning
confidence: 99%
“…This method does not allow for spatial variation in outcomes between national scenarios, making it perhaps better suited to shorter time horizons. A simpler scaling method has been used for Europe, where Terama et al (2017) downscaled national-level age structure projections from a cohort-component model to sub-national regions, proportionally to their age structures in the base year, a method that does not allow for changes over time in the relative age distribution across regions.…”
Section: Introductionmentioning
confidence: 99%
“…Within this analysis, population-centric change, consisting of demographic trends and societal preferences (Terama et al, 2017b), is one of the most significant driver in urban land use development across scenarios (Terama et al, 2017a). Demographic trends are used as an input to the Regional Urbanisation Growth model (RUG).…”
Section: Multi-scale European Sspsmentioning
confidence: 99%
“…The scenario narratives are published in for Europe, in for the Hungarian case study, in Dunn et al (2017) for Scotland and in for Iberia. An overview of the case studies and sectors for decision-making is reported in Lourenço et al (2018) and the summaries of all the local SSPs is provided in the IMPRESSIONS deliverable (Kok & Pedde, 2016 Terama et al (2017b). The focus for this paper is the influence of global scale SSP narratives and European SSP parameterisation, more precisely the links between the total population, age and life-cycle stage, residential preferences and planning (Terama et al, 2017b) on modelling outcomes.…”
Section: Multi-scale European Sspsmentioning
confidence: 99%
See 1 more Smart Citation